Randomand and social security - مريم جبار رشم (College of Education for Women, 2019)
The problem of informal settlements in Iraqi is one of the most serious problems due to its economic, social and security impacts which jeopardize the society safety and stability. This study investigates the present situation of informal settlements in the Baghdad governorates as well as approaches followed in making decisions to either upgrade or remove those areas. Requirements of each decision are also discussed. Study methods relied on both office and field studies to collect data and information needed. The study revealed important findings that would help take appropriate measures that deal with the informal settlements in Iraqi. The study also proposes effective mechanisms to preclude both an increase in current informal settlements' areas and the emergence of new informal settlements.